2021
DOI: 10.1007/s42247-021-00179-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in materials science: a reinforced approach toward challenges against COVID-19

Abstract: With the recent COVID-19 pandemic, medical professionals and scientists have encountered an unprecedented trouble to make the latest technological solutions to work. Despite of abundant tools available as well as initiated for diagnosis and treatment, researchers in the healthcare systems were in backfoot to provide concrete answers to the demanding challenge of SARS-CoV-2. It has incited global collaborative efforts in every field from economic, social, and political to dedicated science to confront the growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…Little work, however, was reported on the influence of the surface morphology on virus inactivation. From this point of view, it should be stressed that many materials used nowadays or proposed to be used in the future in highly efficient masks [61][62][63] exhibit surfaces that might be orders of magnitude larger than the geometrical area. For example, Ahmad et al [64] revealed their thoughts on the healthcare policies, developing materials and technology strategies that have contributed to reducing the damage of the pandemic, coming from the perspectives of material scientists.…”
Section: The Role Of Surfacesmentioning
confidence: 99%
“…Little work, however, was reported on the influence of the surface morphology on virus inactivation. From this point of view, it should be stressed that many materials used nowadays or proposed to be used in the future in highly efficient masks [61][62][63] exhibit surfaces that might be orders of magnitude larger than the geometrical area. For example, Ahmad et al [64] revealed their thoughts on the healthcare policies, developing materials and technology strategies that have contributed to reducing the damage of the pandemic, coming from the perspectives of material scientists.…”
Section: The Role Of Surfacesmentioning
confidence: 99%
“…Through surface functionalization, nanoparticles acquire the ability to interact with specific biomarkers associated with SARS-CoV-2 infection, such as viral proteins, viral RNA, and virus-specific antibodies [9] , [10] . The unique physicochemical properties of nanoparticles, such as their optical, reactivity, or fluorescent properties, enable them to transduce biomarker-capturing events into measurable signals for detection [11] , [12] .…”
Section: Nanoparticle-enabled Detection Of Sars-cov-2mentioning
confidence: 99%
“…Haeberle and Zengerle said that fundamental ideas in the microfluidic device come from the dominant interfacial and surface tensional force in the micro-dimension which enables the precise generation and spatial stabilization of the droplets [3]. Furthermore, microfluidic is widely applied to the following fields: drug delivery [4,5], cell sorting [6][7][8], filtering [9], fluid transport [10], material science [11], chemical engineering [12][13][14], cosmetics production [15], food technology [16], digital polymerase chain reaction (ddPCR) procedure [17], liposomes production [18], liquid metal microdroplets for advance electronics [19], and lab on a chip [3,20]. Zhuo et al have been successful in preparing magnetic thermosensitive hydrogels using microfluidic technology for drug delivery using double emulsions structure with the use of two anticancer drugs: water-soluble drug as the shell and oil-soluble drug in the core which can be released simultaneously by controlling the switch of the magnetic field [4].…”
Section: Introductionmentioning
confidence: 99%